Theoretical Analysis Of The Concept Of "Loneliness" Based On A Psychological Approach - Kamolova, Majnuniso (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes and applies the theoretical aspects of the concept of "Loneliness" based on psychological approaches. It discusses in detail, first of all, the physiological manifestations of the concept of loneliness and their role in psychology. It also applies the fact that the concept of loneliness expresses different meanings and contents in different spaces. That is, in some places it carries a positive meaning, in some places it carries a negative meaning.